Evaluation of lymph node ratio and lymph node yield as prognosticators of locoregional recurrence in p16‐associated oropharyngeal squamous cell carcinoma. Issue 10 (16th June 2020) - Nurimba, Margaret; Hines, William; Sinha, Uttam; Mathew, Anna; Kokot, Niels; Swanson, Mark
Abstract: Background: The prognostic value of lymph node yield (LNY) and lymph node ratio (LNR), or the ratio of number of metastatic LNs to total number dissected, has not been well established in p16‐associated oropharyngeal squamous cell carcinoma (OPSCC). Methods: This retrospective cohort study evaluated locoregional disease‐free survival (LRDFS) in 82 patients with p16+ OPSCC who underwent neck dissection at a single institution from 2009 to 2017. LNR and LNY cutoffs were estimated using time‐dependent receiver operator characteristic (ROC) curves. Prognostic significance of these cutoffs was compared with Eighth Edition AJCC Nodal Staging. Results: An increased LNR ≥ 0.129 was associated with worse 2‐year LRDFS (66.9% vs 96.8%, P = .005). LNY was not significantly associated with LRDFS ( P = .304). An LNR‐based risk model was a better prognosticator than Eighth Edition AJCC Nodal Staging (Harrell's C, 0.9065 vs 0.7668). Conclusions: LNR has good prognostic utility in predicting LRDFS in p16+ OPSCC, but further evaluation of this measure is warranted.